EKPLORASI BENTUK LICHENES DENGAN TEKNIK DIGITAL PRINTING DAN LAMINASS PVC SEBAGAI DECORATIVE TRIMS PADA BUSANA BALL GOWN - Dea Indriani; Mila Karmila (Universitas Pendidikan Indonesia, 2017)
Lichen (licheness) is a compound organism that is a combination of algae and Boletus (mushroom). Lichenes is symbiosis between algae or blue green algaewith fungi of the class Ascomycotina or Basiciomycotina thats structure affect the morphology of lichens. Lichens were widely spread on the surface of the Earth and are able to inhabit the extreme places, like the tundra, a very hard stone surfaces in the mountains or the beach. Based on its form lichens can be distinguished into three groups namely Krutos (like the crust), Folios (such as leaves), and fruktikos (like Bush).The uniqueness of the structure morphology and colour Lichenes have inspired writers to adapt into a dress ball gown as a decoration. Growing fashion trend from time to time. The trend is predicted to have a theme 2017 as